2011
DOI: 10.3748/wjg.v17.i42.4660
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of health-related quality of life after esophagectomy for esophageal cancer

Abstract: This study is aimed to assess the long-term health-related quality of life (HRQL) of patients after esophagectomy for esophageal cancer in comparison with established norms, and to evaluate changes in HRQL during the different stages of follow-up after esophageal resection. A systematic review was performed by searching medical databases (Medline, Embase and the Cochrane Library) for potentially relevant studies that appeared between January 1975 and March 2011. Studies were included if they addressed the ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
104
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 66 publications
5
104
0
Order By: Relevance
“…The most significant areas where surgical patients suffer are predictably related to loss of their stomach's normal function: eating problems, reflux symptoms, loss of appetite, and diarrhea. However, these patients also had worse scores with general health measures like fatigue and dyspnea, and experienced lower overall physical function, vitality scores, and health perception than controls long-term (43). Notably, organ preservation in esophageal cancer patients has been shown to be predictive of global measures of HRQOL (44).…”
Section: Quality Of Life Considerationsmentioning
confidence: 99%
“…The most significant areas where surgical patients suffer are predictably related to loss of their stomach's normal function: eating problems, reflux symptoms, loss of appetite, and diarrhea. However, these patients also had worse scores with general health measures like fatigue and dyspnea, and experienced lower overall physical function, vitality scores, and health perception than controls long-term (43). Notably, organ preservation in esophageal cancer patients has been shown to be predictive of global measures of HRQOL (44).…”
Section: Quality Of Life Considerationsmentioning
confidence: 99%
“…The incidence of esophageal cancer has been increasing steadily in the past few decades; along with thyroid cancer, it has become the fastest rising solid tumor in the Western hemisphere (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Patients have problems with appetite loss, dysphagia, regurgitation, early satiety and consequently, weight loss along with other issues like diarrhea and fatigue (2,14,15). Thus, the assessment of the effect of treatment on health-related quality of life (HRQOL) before, during and after treatment time is important for patients, caregivers and clinicians (15).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that technical surgical complications had significant deleterious effects on quality of life; however, there was no significant overall deterioration in quality of life associated with the more extensive operative approaches in the absence of major postoperative complications. Multiple additional reports have highlighted that the single most important issue associated with poor quality of life is the occurrence of perioperative complications [50,51,52]. …”
Section: Esophageal Resection and Quality Of Lifementioning
confidence: 99%